Association between Helicobacter pylori infection, serum thyroid-stimulating hormone, and thyroxine in the National Health and Nutrition Examination Survey 1999–2000 - Lu, Ting; Lu, Shunshun; Lin, Jieqiong; Shao, Xiaona; Chen, Dahua; Shen, Jianwei (Frontiers in Endocrinology, 2025)
BackgroundHelicobacter pylori has been increasingly implicated in extra-gastric diseases. Current evidence regarding the association between serum thyroid-stimulating hormone (TSH), thyroxine (T4), and H. pylori infection remains inconclusive. Consequently, this study aimed to explore the correlation between TSH and T4 levels and H. pylori infection in a US-based population sample.MethodsData from the US National Health and Nutrition Examination Survey (NHANES), comprising 971 participants aged 30–85 years from 1999 to 2000, were analyzed. Binary logistic regression was employed to analyze the correlation between H. pylori and TSH and T4 levels. The impact of TSH and T4 on H. pylori infection was further assessed using restricted cubic spline (RCS) analysis. In addition, subgroup analyses stratified by sex and age were conducted.ResultsSubjects with H. pylori seropositivity demonstrated lower serum TSH levels and higher serum T4 levels compared to those with H. pylori seronegativity. A significant positive correlation was identified between H. pylori seropositivity and T4 levels with increasing quartiles of hormonal levels in both univariate regression models (Q4 vs. Q1: OR = 1.483; 95% CI, 1.033–2.129) and multivariate regression models (Q4 vs. Q1: OR = 1.004; 95% CI, 0.981–1.026). Conversely, a negative correlation was observed between H. pylori seropositivity and TSH levels with increasing quartiles of hormonal levels in univariate regression models (Q4 vs. Q1: OR = 0.579; 95% CI, 0.403–0.831) and in multivariate regression models (Q4 vs. Q1: OR = 0.580; 95% CI, 0.389–0.866). In stratified analyses, the adjusted association of serum T4 levels with H. pylori seropositivity was statistically significant among men (T4: Q4 vs. Q1: OR = 2.253; 95% CI, 1.311–3.873), age over 68 years in TSH levels (Q4 vs. Q1: OR = 0.434; 95% CI, 0.206–0.911), and age 41–54 years in T4 levels (Q4 vs. Q1: OR = 4.965; 95% CI, 2.071–11.903). RCS analysis revealed a non-linear relationship between TSH levels and H. pylori infection. Notably, when TSH < 0.98 IU/ml, the likelihood of H. pylori infection significantly increased.ConclusionsLower TSH and higher T4 levels were associated with H. pylori infection, particularly among men and elderly individuals.